2021
DOI: 10.3892/or.2021.8000
|View full text |Cite
|
Sign up to set email alerts
|

Oncolytic adenovirus: A tool for reversing the tumor microenvironment and promoting cancer treatment (Review)

Abstract: Immunogene therapy can enhance the antitumor immune effect by introducing genes encoding co-stimulation molecules, cytokines, chemokines and tumor-associated antigens into treatment cells or human cells through genetic engineering techniques. Oncolytic viruses can specifically target tumor cells and replicate indefinitely until they kill tumor cells. If combined with immunogene therapy, oncolytic viruses can play a more powerful antitumor role. The high pressure, hypoxia and acidity in the tumor microenvironme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 108 publications
0
16
0
Order By: Relevance
“…Immune checkpoints are regulatory molecules that play an inhibitory role in the immune system, 37 and they are essential for maintaining self-tolerance, preventing autoimmune response, and minimizing tissue damage by controlling the time and intensity of immune response. 38,39 The function of immune cells can be inhibited by the expression of immune checkpoint molecules on them, which makes the body unable to produce effective anti-tumour immune response, thus forming immune escape of tumours. 40 We found that the immune scores and immune checkpoint expression in CIC, IDH1 and ARID1A mutant group were obviously lower than that in wildtype, suggesting that the body can better recognize the mutated antigen cells and promote the immune function of T cells to better remove the antigen and inhibit tumour development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immune checkpoints are regulatory molecules that play an inhibitory role in the immune system, 37 and they are essential for maintaining self-tolerance, preventing autoimmune response, and minimizing tissue damage by controlling the time and intensity of immune response. 38,39 The function of immune cells can be inhibited by the expression of immune checkpoint molecules on them, which makes the body unable to produce effective anti-tumour immune response, thus forming immune escape of tumours. 40 We found that the immune scores and immune checkpoint expression in CIC, IDH1 and ARID1A mutant group were obviously lower than that in wildtype, suggesting that the body can better recognize the mutated antigen cells and promote the immune function of T cells to better remove the antigen and inhibit tumour development.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we also found these six mutated genes were significantly correlated with the immune score and immune checkpoints. Immune checkpoints are regulatory molecules that play an inhibitory role in the immune system, 37 and they are essential for maintaining self‐tolerance, preventing autoimmune response, and minimizing tissue damage by controlling the time and intensity of immune response 38,39 . The function of immune cells can be inhibited by the expression of immune checkpoint molecules on them, which makes the body unable to produce effective anti‐tumour immune response, thus forming immune escape of tumours 40 .…”
Section: Discussionmentioning
confidence: 99%
“…However, many tumor cells are evolved to produce immune-inhibitory factors such as IL-10, TGF-β, and vascular endothelial growth factor (VEGF), which minimize the efficacy of the dendritic cells (Elmusrati et al, 2021, Farlow et al, 2021. Modifications of the adenovirus including the inclusion of a repressor for VEGF expression in the tumor cell could help promote dendritic cell efficacy and allow for increased immune response (Goradel et al, 2019, Wang, Zhong, et al, 2021.…”
Section: Activation Of Immune and Vaccination Responses By Adenovirusesmentioning
confidence: 99%
“…Current research with smart oncolytic viruses focuses on two main hallmarks of cancer: the ability of cancer cells to evade the immune system and programmed cell death and their resistance to inhibitory signals preventing their growth (Wang, Zhong, et al, 2021). Multiple interconnected pathways between cancer and cells of the immune system converge in the development of a tumor environment where cancer cells can evade immune detection and programmed cell death (Huang et al, 2016).…”
Section: Genetic Engineering Of Recombinant Adenoviruses Expressing Immuno-stimulatory Molecules Can Increase Tumor-targeted Immune Respomentioning
confidence: 99%
See 1 more Smart Citation